Defining the Need for and Proposing How to Transform Traditional into Digital Banks with the Support of Information and Mobile Technologies - Sajić, Mirko; Bundalo, Zlatko; Bundalo, Dušanka (The European Journal of Applied Economics, 2019)
The need to practically and effectively implement the transformation of standard traditional banks into digital ones and how to transform them using information and mobile technologies are analyzed and described in the paper. The aim of this paper is to provide clear evidence about the need to transform banks from their present, traditional form into a new one that organizes and provides services, through a so-called digital bank. The great influence of mobile digital information technologies on the entire financial sector is further emphasized. The problems that appear because of the divergence of the existing concept of bank development and way in which modern clients want to obtain services, according to the possibilities of modern mobile digital technologies, are addition-ally explained. Proposals are also given for how to practically perform these changes and transformations, together with reasons that require changes. The basic principles for transitioning banks from traditional to digital formats through the so-called hybrid transformation period are presented, and several concrete solutions are proposed.